High-firmness fiber textile composite material and preparation method thereof

By adding polyester chopped wire fibers, silane modified alumina particles and nanolignin polyol-based epoxy resin to the fiber textile composite material, combined with the modification treatment of carbon fiber and aramid fiber, the fiber textile composite material machinery is solved. The problem of insufficient performance, corrosion resistance and thermal stability has achieved the preparation of fiber textile composite materials with high firmness and long life.

CN119189454AInactive Publication Date: 2024-12-27NANTONG HUAJINCHENG CHEM FIBER TECH CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411710649.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing fiber textile composite materials have shortcomings in mechanical properties, corrosion resistance, thermal stability and service life, which leads to easy damage or breakage during application, short service life and small application range.

Method used

Modification of carbon fiber and aramid fiber by adding polyester chopped wire fibers to the polyterephthalyl terephthalyl terephthalyl diamine solution, using silane-modified alumina particles and nanolignin polyol-based epoxy resin, combined with carbon fiber and aramid fibers The fiber textile composite material with high firmness was prepared by curing it by a double-layer flat plate vulcanization hydraulic press to prepare a fiber textile composite material with improved mechanical properties, corrosion resistance and thermal stability.

Benefits of technology

It significantly improves the mechanical properties, corrosion resistance and thermal stability of fiber textile composite materials, extends service life, expands the scope of application, and avoids structural instability and corrosion of fiber textile composite materials in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119189454A_ABST
    Figure CN119189454A_ABST
Patent Text Reader

Abstract

The invention discloses a high-firmness fiber textile composite material and a preparation method thereof, and relates to the technical field of textile composite materials. The preparation method of the fiber prepreg comprises the following steps: mixing nano lignin polyol-based epoxy resin, an acetone solution, silane-modified alumina particles and a curing agent, smearing the mixture on a wet gel fiber fabric, a modified carbon fiber cloth and an aramid fiber fabric, and drying to obtain the fiber prepreg. Laying the modified carbon fiber cloth coated with the mixture, the aramid fiber fabric and the wet gel fiber fabric layer by layer to obtain the fiber prepreg. According to the invention, the polyester chopped strand fiber is added into the poly-p-phenylene terephthamide solution, so that the mechanical property of the aerogel fiber is improved, the mechanical property of the fiber textile composite material is enhanced, and the application range of the fiber textile composite material is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile composite materials, in particular to a high-firmness fiber textile composite material and a preparation method thereof. Background Art

[0002] With the continuous progress of science and technology and the rapid development of industrialization, people's requirements for material performance are gradually increasing. Among many materials, fiber textile composite materials have attracted increasing attention due to their light weight, high strength, corrosion resistance, fatigue resistance and other characteristics.

[0003] Fiber materials, as reinforcements of composite materials, can significantly improve the mechanical properties and firmness of fiber textile composite materials. Epoxy resin matrix materials, as another important component of fiber textile composite materials, have properties that directly affect the overall properties of the composite materials. Therefore, a fiber textile composite material with high firmness and a preparation method thereof are extremely important.

[0004] 1. Patent document CN105818492B discloses a bioactive phosphate-based continuous glass fiber textile composite material and its use. The above patent achieves that the mechanical properties of the composite material reach the level of human bones, and the mechanical properties match those of bone tissue, but the above patent cannot achieve the function of improving the mechanical properties of the fiber textile composite material.

[0005] 2. Patent document CN108456933B discloses a method for preparing lignin-rich fibers for textiles and composite materials by high-temperature directional degumming. The above patent achieves a composite material tensile breaking strength that is more than 50% higher than that of a composite material made of lignin-rich fibers after conventional alkali degumming, and a bending strength that is more than 80% higher. However, the above patent cannot achieve an improvement in the corrosion resistance of the fiber textile composite material.

[0006] 3. Patent document CN104097358B discloses a nanofiber composite material with anti-ultraviolet function and a method for manufacturing the same. The above patent achieves high-performance anti-ultraviolet effect of the fabric and good moisture absorption and breathability, but the above patent cannot achieve high firmness of the fiber textile composite material.

[0007] 4. Patent document CN111485328B discloses a method and device for preparing a flame-retardant nanofiber composite material. The above patent realizes that the composite material is flame-retardant and flame-resistant, has excellent filtering performance, and has a strong adsorption capacity for smoke and harmful gases. However, the above patent cannot realize that the fiber textile composite material has good thermal stability.

[0008] In summary, the above patents cannot achieve the function of improving the mechanical properties of fiber textile composite materials, cannot achieve the improvement of the corrosion resistance of fiber textile composite materials, cannot achieve the high firmness of fiber textile composite materials, and cannot achieve the function of fiber textile composite materials having good thermal stability, resulting in the problem of easy damage or breakage during application, short service life, and small application range; To this end, the present application proposes a fiber textile composite material and a preparation method thereof that can improve the mechanical properties of the fiber textile composite material, improve the corrosion resistance of the fiber textile composite material, achieve high firmness of the fiber textile composite material, and achieve good thermal stability and high firmness of the fiber textile composite material. Summary of the invention

[0009] The object of the present invention is to provide a fiber textile composite material with high firmness and a preparation method thereof, so as to solve the technical problems proposed in the above-mentioned background technology that the fiber textile composite material cannot achieve the function of improving the mechanical properties, cannot achieve the improvement of the corrosion resistance, cannot achieve the high firmness of the fiber textile composite material, cannot achieve the function of having good thermal stability of the fiber textile composite material, resulting in easy damage or breakage during application, short service life and small application range.

[0010] To achieve the above object, the present invention provides the following technical solution: a fiber textile composite material with high firmness, comprising a fiber prepreg, wherein the preparation method of the fiber prepreg comprises the following steps: Step 1: Add polyester chopped fibers into a poly(p-phenylene terephthalamide) solution, use a high-speed centrifuge to centrifuge to remove bubbles in the solution, and squeeze the degassed solution through a spinneret into a coagulation bath to obtain wet gel fibers; Step 2: washing the wet gel fiber with deionized water and tert-butyl alcohol aqueous solution in turn, placing the treated wet gel fiber in a refrigerator for freezing treatment, placing the frozen wet gel fiber in a freeze dryer for drying treatment to obtain aerogel fiber, and weaving the aerogel fiber into aerogel fiber fabric; Step 3: Mix the nano-lignin polyol-based epoxy resin, acetone solution, silane-modified alumina particles and curing agent, apply the mixture on wet gel fiber fabric, modified carbon fiber cloth and aramid fiber fabric, lay the modified carbon fiber cloth, aramid fiber fabric and wet gel fiber fabric coated with the mixture layer by layer, let it stand for 24 hours, and obtain a fiber prepreg.

[0011] Preferably, the method for preparing the poly(p-phenylene terephthalamide) solution comprises the following steps: Step 1: nitrogen is filled into a reaction vessel, N-methylpyrrolidone and calcium chloride are added, the reaction vessel is placed in a water bath and stirred until the calcium chloride is completely dissolved, and p-phenylenediamine is added to the reaction vessel after cooling to room temperature; Step 2: Place the reaction container in a freezing bath, add phthaloyl chloride, stir with a magnetic stirrer for 45 minutes, take out the reaction container and place it in a room temperature environment, stir to obtain a poly(p-phenylene terephthalamide) solution.

[0012] Preferably, the method for preparing the modified carbon fiber cloth comprises the following steps: Step 1: Spread the carbon fiber cloth flat in the reaction tank, add acetone solution until the liquid level covers the carbon fiber cloth, and perform water bath treatment in a sealed space. Take it out after 2 days of water bath and wash it with distilled water; Step 2: Place the washed carbon fiber in a vacuum drying oven for drying, soak the dried carbon fiber cloth in concentrated nitric acid, wash with distilled water after a 3-hour water bath, and dry in a vacuum drying oven to obtain a modified carbon fiber cloth.

[0013] Preferably, the method for preparing the silane-modified alumina particles comprises the following steps: Step 1: adding silane to an ethanol solution, stirring with a magnetic stirrer to obtain a silane ethanol solution, adding the ethanol solution to a reaction container, dissolving alumina particles in the ethanol solution, adding deionized water, placing the reaction container in a water bath, and continuously stirring to obtain a mixed solution; Step 2: slowly add the silane ethanol solution to the mixed solution, mix well and place in a water bath for stirring. After the reaction is completed, use a suction filtration device to filter the reaction solution, and wash with anhydrous ethanol after the filtration is completed; Step 3: Place the washed product in a drying oven for drying, and grind the product using a grinder to obtain silane-modified alumina particles.

[0014] Preferably, the preparation method of the nano-lignin polyol-based epoxy resin comprises the following steps: Step 1: Add nano-lignin polyol and epichlorohydrin in a reaction container in sequence, stir with a magnetic stirrer, add bisphenol A particles, place the mixture in a water bath, and stir; Step 2: Add sodium hydroxide solution to the mixture, stir and mix, let it stand for 2 hours and then perform distillation treatment, cool the distilled product to room temperature to obtain nano-lignin polyol-based epoxy resin.

[0015] Preferably, the preparation method of the nano-lignin polyol comprises the following steps: Step 1: dissolving the modified lignin in an ethylene glycol solution to obtain a lignin solution, placing the lignin solution in a water bath, stirring, and adding a sulfuric acid solution dropwise into the reaction solution to adjust the pH; Step 2: Filter the solution using hardened ash-free filter paper, pour the filtered solution into a dialysis bag, perform dialysis treatment in deionized water, add distilled water to dilute the treated solution, and perform ultrasonic treatment on the diluted solution to obtain a nano-lignin suspension; Step 3: Add ethylene glycol, propylene glycol and catalyst methanesulfonic acid to the nano-lignin suspension, place the mixture in an oil bath at 120° C. for 1 hour, cool to room temperature, add sodium hydroxide solution dropwise to the reactant, adjust the pH, and obtain nano-lignin-based polyol.

[0016] Preferably, the preparation method of the modified lignin comprises the following steps: Step 1: adding lignin to distilled water, stirring with a stirrer to disperse the lignin in the water to obtain a uniform suspension, adding sodium hydroxide solution to the suspension, and stirring; Step 2: Add formaldehyde solution, place the mixed solution in a water bath for 5 hours, slowly add sulfuric acid solution after the reaction is completed, use a high-speed centrifuge for centrifugation, wash the product obtained by centrifugation with distilled water, and place the washed product in a vacuum drying oven to obtain modified lignin.

[0017] Preferably, the method for preparing the aramid fiber fabric comprises the following steps: Step 1: dissolving calcium chloride in anhydrous ethanol to obtain an ethanol solution of calcium chloride, placing the aramid fiber in a reaction tank, immersing the aramid fiber in the ethanol solution of calcium chloride, and placing the reaction tank in a water bath; Step 2: Take out the aramid fiber, wash it with deionized water, put the washed aramid fiber in a vacuum drying oven for drying, and obtain aramid fiber fabric.

[0018] Preferably, the method for preparing the fiber textile composite material comprises the following steps: S1. Stack the fiber prepregs alternately, place them in a mold equipped with a release cloth, and wrap the outer layer of the mold with tin foil; S2. Place the mold in a double-layer flat plate vulcanizing hydraulic press for curing, cool to room temperature, and demould to obtain a fiber textile composite material.

[0019] Preferably, the method for preparing the composite material further comprises the following steps: S21. Clean the composite material after demoulding, remove excess demoulding cloth and resin, and cut the composite material according to needs.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention improves the mechanical properties of aerogel fibers and fiber textile composite materials by adding polyester chopped strands into poly(p-phenylene terephthalamide) solution, thereby enhancing the mechanical properties of fiber textile composite materials and increasing the application range of fiber textile composite materials; 2. The present invention adds silane-modified alumina particle corrosion-resistant filler into the epoxy resin matrix to prevent the erosion of the corrosive medium on the fiber, thereby improving the corrosion resistance of the fiber textile composite material and increasing the service life of the fiber textile composite material; 3. The present invention improves the bonding strength between the fiber and the epoxy resin matrix through surface modification of the carbon fiber and aramid fiber, improves the overall mechanical properties of the composite material, and achieves high firmness of the fiber textile composite material; 4. The present invention improves the thermal stability of the fiber textile composite material and the dispersibility of the filler by using a nano-lignin polyol-based epoxy resin matrix material with high heat resistance and a silane-modified alumina particle filler. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of the preparation process of the fiber prepreg of the present invention; Figure 2 This is a schematic diagram of the preparation process of the aerogel fiber fabric of the present invention; Figure 3 This is a schematic diagram of the preparation process of the modified carbon fiber cloth of the present invention; Figure 4 This is a schematic diagram of the preparation process of the aramid fiber fabric of the present invention; Figure 5 This is a schematic diagram of the preparation process of silane-modified alumina particles of the present invention; Figure 6 This is a schematic diagram of the epoxy resin preparation process of the present invention; Figure 7 This is a schematic diagram of the preparation process of nano-lignin polyol of the present invention; Figure 8 The figure is a schematic diagram of the preparation process of the modified lignin of the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1, please refer to Figure 1 and Figure 2 , a fiber textile composite material with high firmness, the preparation method of the fiber textile composite material comprising the following steps: Step 1: nitrogen is filled into a reaction container, N-methylpyrrolidone and calcium chloride are added, the reaction container is placed in a water bath and stirred until the calcium chloride is completely dissolved, p-phenylenediamine is added to the reaction container after cooling to room temperature, the reaction container is placed in a freezing bath, phthaloyl chloride is added, and a magnetic stirrer is used to stir for 45 minutes, the reaction container is taken out and placed in a room temperature environment, and stirred to obtain a poly(p-phenylene terephthalamide) solution; Step 2: adding polyester chopped fibers to a poly(p-phenylene terephthalamide) solution, centrifuging with a high-speed centrifuge to remove bubbles in the solution, squeezing the degassed solution through a spinneret into a coagulation bath to obtain wet gel fibers, washing the wet gel fibers with deionized water and tert-butyl alcohol aqueous solution in turn, placing the treated wet gel fibers in a refrigerator for freezing treatment, placing the frozen wet gel fibers in a freeze dryer for drying treatment to obtain aerogel fibers, and weaving the aerogel fibers into aerogel fiber fabrics; Step 3: Mix the nano-lignin polyol-based epoxy resin, acetone solution, silane-modified alumina particles and curing agent, apply the mixture on wet gel fiber fabric, modified carbon fiber cloth and aramid fiber fabric, lay the modified carbon fiber cloth, aramid fiber fabric and wet gel fiber fabric coated with the mixture layer by layer, let it stand for 24 hours to obtain fiber prepreg, alternately stack the fiber prepregs, place them in a mold with a demolding cloth, wrap the outer layer of the mold with tin foil, place the mold in a double-layer flat vulcanizing hydraulic press, perform curing treatment, cool to room temperature, and perform demolding treatment to obtain a fiber textile composite material; Furthermore, polyester chopped fibers are added to the poly(p-phenylene terephthalamide) solution to form a macroscopic fiber network in the solution. In the subsequent spinning and coagulation process, the continuity and stability of the fibers can be maintained, thereby reducing fiber breakage and loss. The addition of polyester chopped fibers effectively improves the dispersibility of the poly(p-phenylene terephthalamide) solution in the spinning process, making the spun wet gel fibers more uniform, thereby forming a denser and more uniform aerogel fiber structure. Polyester chopped fibers can improve the mechanical properties of aerogel fibers, further enhance the mechanical properties of aerogel fibers, and improve the tensile strength, tear strength and other properties of aerogel fibers. Example 2, please refer to Figure 1 and Figure 4 , a fiber textile composite material with high firmness, the preparation method of the fiber textile composite material comprising the following steps: Step 1: adding polyester chopped fibers to a poly(p-phenylene terephthalamide) solution, centrifuging with a high-speed centrifuge to remove bubbles in the solution, squeezing the degassed solution through a spinneret into a coagulation bath to obtain wet gel fibers, washing the wet gel fibers with deionized water and tert-butyl alcohol aqueous solution in turn, placing the treated wet gel fibers in a refrigerator for freezing treatment, placing the frozen wet gel fibers in a freeze dryer for drying treatment to obtain aerogel fibers, and weaving the aerogel fibers into aerogel fiber fabrics; Step 2: dissolving calcium chloride in anhydrous ethanol to obtain an ethanol solution of calcium chloride, placing aramid fiber in a reaction tank, immersing the aramid fiber in the ethanol solution of calcium chloride, placing the reaction tank in a water bath, taking out the aramid fiber, washing it with deionized water, placing the washed aramid fiber in a vacuum drying oven, drying it, and obtaining aramid fiber fabric; Step 3: Mix the nano-lignin polyol-based epoxy resin, acetone solution, silane-modified alumina particles and curing agent, apply the mixture on wet gel fiber fabric, modified carbon fiber fabric and aramid fiber fabric, lay the modified carbon fiber fabric, aramid fiber fabric and wet gel fiber fabric coated with the mixture layer by layer, and let it stand for 24 hours to obtain a fiber prepreg; Furthermore, calcium chloride complexes with the amide groups in the aramid fiber molecular chain, reducing the crystallinity of the aramid fiber surface, resulting in uneven spots and grooves on the surface of the aramid fiber, thereby increasing the roughness of the aramid fiber surface, enhancing the mechanical bite force and bonding area between the aramid fiber and the nano-lignin polyol-based epoxy resin, thereby increasing the bonding strength between the two, avoiding interface slip and debonding between the aramid fiber and the nano-lignin polyol-based epoxy resin, thereby improving the overall mechanical properties of the composite material, and making the fiber textile composite material highly firm.

[0024] Example 3, please refer to Figure 1 and Figure 5 , a fiber textile composite material with high firmness, the preparation method of the fiber textile composite material comprising the following steps: Step 1: adding polyester chopped fibers to a poly(p-phenylene terephthalamide) solution, centrifuging with a high-speed centrifuge to remove bubbles in the solution, squeezing the degassed solution through a spinneret into a coagulation bath to obtain wet gel fibers, washing the wet gel fibers with deionized water and tert-butyl alcohol aqueous solution in turn, placing the treated wet gel fibers in a refrigerator for freezing treatment, placing the frozen wet gel fibers in a freeze dryer for drying treatment to obtain aerogel fibers, and weaving the aerogel fibers into aerogel fiber fabrics; Step 2: adding silane to an ethanol solution, stirring with a magnetic stirrer to obtain a silane ethanol solution, adding the ethanol solution to a reaction vessel, dissolving alumina particles in the ethanol solution, adding deionized water, placing the reaction vessel in a water bath, and continuously stirring to obtain a mixed solution, slowly adding the silane ethanol solution to the mixed solution, mixing evenly, placing in a water bath, and stirring, filtering the reaction solution with a suction filtration device after the reaction is completed, washing with anhydrous ethanol, placing the washed product in a drying oven for drying, and grinding the product with a grinder to obtain silane-modified alumina particles; Step 3: Mix the nano-lignin polyol-based epoxy resin, acetone solution, silane-modified alumina particles and curing agent, apply the mixture on wet gel fiber fabric, modified carbon fiber fabric and aramid fiber fabric, lay the modified carbon fiber fabric, aramid fiber fabric and wet gel fiber fabric coated with the mixture layer by layer, and let it stand for 24 hours to obtain a fiber prepreg; Furthermore, the alumina particles have certain strength and hardness. After being modified by silane, the dispersibility of the alumina particles is improved, so that the silane-modified alumina particles are evenly distributed in the nano-lignin polyol-based epoxy resin matrix, thereby effectively transferring and dispersing the load, thereby improving the overall mechanical properties of the composite material. At the same time, the modified alumina particles can reduce the stress concentration phenomenon in the nano-lignin polyol-based epoxy resin matrix, and avoid local damage to the fiber textile composite material when subjected to external forces; As a material with high melting point and high thermal stability, alumina can significantly improve the heat resistance of fiber-textile composite materials by filling silane-modified alumina particles into composite materials, so that the fiber-textile composite materials can still maintain good mechanical properties and structural stability under high temperature environment. Silane-modified alumina is evenly dispersed in the nano-lignin polyol-based epoxy resin matrix, which produces more barriers in the matrix, prolongs the path of corrosive media, effectively resists the erosion of corrosive media, and prolongs the service life of fiber-textile composite materials.

[0025] Example 4, please refer to Figure 1 and Figure 3 , a fiber textile composite material with high firmness, the preparation method of the fiber textile composite material comprising the following steps: Step 1: adding polyester chopped fibers to a poly(p-phenylene terephthalamide) solution, centrifuging with a high-speed centrifuge to remove bubbles in the solution, squeezing the degassed solution through a spinneret into a coagulation bath to obtain wet gel fibers, washing the wet gel fibers with deionized water and tert-butyl alcohol aqueous solution in turn, placing the treated wet gel fibers in a refrigerator for freezing treatment, placing the frozen wet gel fibers in a freeze dryer for drying treatment to obtain aerogel fibers, and weaving the aerogel fibers into aerogel fiber fabrics; Step 2: Spread the carbon fiber cloth flat in the reaction tank, add acetone solution until the liquid level covers the carbon fiber cloth, carry out water bath treatment in a sealed space, take out after 2 days of water bath, wash with distilled water, place the washed carbon fiber cloth in a vacuum drying oven for drying, soak the dried carbon fiber cloth with concentrated nitric acid, wash with distilled water after 3 hours of water bath, and dry in a vacuum drying oven to obtain a modified carbon fiber cloth; Step 3: Mix the nano-lignin polyol-based epoxy resin, acetone solution, silane-modified alumina particles and curing agent, apply the mixture on wet gel fiber fabric, modified carbon fiber fabric and aramid fiber fabric, lay the modified carbon fiber fabric, aramid fiber fabric and wet gel fiber fabric coated with the mixture layer by layer, and let it stand for 24 hours to obtain a fiber prepreg; Furthermore, the modification of the carbon fiber cloth improves the roughness of the carbon fiber surface, increases the contact area and mechanical bite force between the carbon fiber and the nano-lignin polyol-based epoxy resin, thereby improving the bonding force between the two, making the fiber textile composite material highly firm, and avoiding damage to the fiber textile composite material due to interface debonding during use. At the same time, the modified carbon fiber cloth can better combine with the epoxy resin matrix, thereby reducing defects such as bubbles and holes at the interface, thereby improving the overall density of the fiber textile composite material, making the bond between the modified carbon fiber cloth and the resin matrix more firm, thereby improving the overall strength and modulus of the fiber textile composite material. In addition, the modified carbon fiber cloth can effectively resist cyclic loads and impact loads, thereby improving the durability and service life of the fiber textile composite material.

[0026] Example 5, please refer to Figure 1 , Figure 6 , Figure 7 and Figure 8 , a fiber textile composite material with high firmness, the preparation method of the fiber textile composite material comprising the following steps: Step 1: adding polyester chopped fibers to a poly(p-phenylene terephthalamide) solution, centrifuging with a high-speed centrifuge to remove bubbles in the solution, squeezing the degassed solution through a spinneret into a coagulation bath to obtain wet gel fibers, washing the wet gel fibers with deionized water and tert-butyl alcohol aqueous solution in turn, placing the treated wet gel fibers in a refrigerator for freezing treatment, placing the frozen wet gel fibers in a freeze dryer for drying treatment to obtain aerogel fibers, and weaving the aerogel fibers into aerogel fiber fabrics; Step 2: Add lignin to distilled water, stir with a stirrer, disperse lignin in water to obtain a uniform suspension, add sodium hydroxide solution to the suspension, stir, add formaldehyde solution, place the mixed solution in a water bath for 5 hours, slowly add sulfuric acid solution after the reaction is completed, centrifuge with a high-speed centrifuge, wash the product obtained by centrifugation with distilled water, place the washed product in a vacuum drying oven to obtain modified lignin, dissolve the modified lignin in ethylene glycol solution to obtain a lignin solution, place the lignin solution in a water bath, stir stirring, adding sulfuric acid solution dropwise into the reaction solution to adjust the pH, filtering the solution using hardened ash-free filter paper, pouring the filtered solution into a dialysis bag, dialyzing it in ionized water, adding distilled water to dilute the treated solution, ultrasonically treating the diluted solution to obtain a nano-lignin suspension, adding ethylene glycol, propylene glycol and catalyst methanesulfonic acid to the nano-lignin suspension, placing the mixture in an oil bath at 120° C. for 1 h, cooling it to room temperature, adding sodium hydroxide solution dropwise into the reactant to adjust the pH to obtain a nano-lignin-based polyol; Step 3: Mix the nano-lignin polyol-based epoxy resin, acetone solution, silane-modified alumina particles and curing agent, apply the mixture on wet gel fiber fabric, modified carbon fiber fabric and aramid fiber fabric, lay the modified carbon fiber fabric, aramid fiber fabric and wet gel fiber fabric coated with the mixture layer by layer, and let it stand for 24 hours to obtain a fiber prepreg; Furthermore, the nano-lignin polyol-based epoxy resin improves the preparation of highly active and pollution-free nano-lignin particles, thereby reducing the consumption of limited petroleum resources and reducing environmental pollution in the production process. The nano-lignin polyol-based epoxy resin is used as a matrix resin for fiber textile composite materials. Its molecular chain contains a large number of epoxy groups, which can undergo cross-linking reactions with curing agents, silane-modified alumina particles, etc. to form a stable three-dimensional network structure, thereby improving the matrix strength of the fiber textile composite material, and then improving the mechanical properties of the fiber textile composite material. The nano-lignin polyol-based epoxy resin has good thermal stability, so that the fiber textile composite material can maintain good mechanical properties under high temperature conditions.

[0027] Example 6, please refer to Figure 1 , a fiber textile composite material with high firmness, the preparation method of the fiber textile composite material comprising the following steps: Step 1: Mix nano-lignin polyol-based epoxy resin, acetone solution, silane-modified alumina particles and curing agent, apply the mixture on modified carbon fiber cloth and aramid fiber fabric, lay the modified carbon fiber cloth and aramid fiber fabric coated with the mixture layer by layer, and let it stand for 24 hours to obtain a fiber prepreg; Step 2: stack the fiber prepregs alternately and place them in a mold equipped with a demoulding cloth, wrap the outer layer of the mold with tin foil, place the mold in a double-layer flat-plate vulcanizing hydraulic press, perform curing treatment, cool to room temperature, and perform demoulding treatment to obtain a fiber textile composite material.

[0028] Comparative Example 1, a fiber textile composite material with high firmness, wherein the preparation method of the fiber textile composite material comprises the following steps: Step 1: nitrogen is filled into a reaction container, N-methylpyrrolidone and calcium chloride are added, the reaction container is placed in a water bath and stirred until the calcium chloride is completely dissolved, p-phenylenediamine is added to the reaction container after cooling to room temperature, the reaction container is placed in a freezing bath, phthaloyl chloride is added, and a magnetic stirrer is used to stir for 45 minutes, the reaction container is taken out and placed in a room temperature environment, and stirred to obtain a poly(p-phenylene terephthalamide) solution; Step 2: centrifuge the poly(p-phenylene terephthalamide) solution using a high-speed centrifuge to remove bubbles in the solution, squeeze the degassed solution through a spinneret into a coagulation bath to obtain wet gel fibers, wash the wet gel fibers with deionized water and tert-butyl alcohol aqueous solution in turn, put the treated wet gel fibers into a refrigerator for freezing treatment, put the frozen wet gel fibers into a freeze dryer for drying treatment to obtain aerogel fibers, and weave the aerogel fibers into aerogel fiber fabrics; Step 3: Mix the nano-lignin polyol-based epoxy resin, acetone solution, silane-modified alumina particles and curing agent, apply the mixture on wet gel fiber fabric, modified carbon fiber cloth and aramid fiber fabric, lay the modified carbon fiber cloth, aramid fiber fabric and wet gel fiber fabric coated with the mixture layer by layer, let it stand for 24 hours to obtain fiber prepreg, alternately stack the fiber prepregs, place them in a mold with a release cloth, wrap tin foil on the outer layer of the mold, place the mold in a double-layer flat plate vulcanizing hydraulic press, perform curing treatment, cool to room temperature, and perform demolding to obtain a fiber textile composite material.

[0029] Comparative Example 2, a fiber textile composite material with high firmness, wherein the preparation method of the fiber textile composite material comprises the following steps: Step 1: nitrogen is filled into a reaction container, N-methylpyrrolidone and calcium chloride are added, the reaction container is placed in a water bath and stirred until the calcium chloride is completely dissolved, p-phenylenediamine is added to the reaction container after cooling to room temperature, the reaction container is placed in a freezing bath, phthaloyl chloride is added, and a magnetic stirrer is used to stir for 45 minutes, the reaction container is taken out and placed in a room temperature environment, and stirred to obtain a poly(p-phenylene terephthalamide) solution; Step 2: adding polyester chopped fibers to a poly(p-phenylene terephthalamide) solution, centrifuging with a high-speed centrifuge to remove bubbles in the solution, squeezing the degassed solution through a spinneret into a coagulation bath to obtain wet gel fibers, washing the wet gel fibers with deionized water and tert-butyl alcohol aqueous solution in turn, placing the treated wet gel fibers in a refrigerator for freezing treatment, placing the frozen wet gel fibers in a freeze dryer for drying treatment to obtain aerogel fibers, and weaving the aerogel fibers into aerogel fiber fabrics; Step 3: Mix the nano-lignin polyol-based epoxy resin, acetone solution, silane-modified alumina particles and curing agent, apply the mixture on wet gel fiber fabric and aramid fiber fabric, lay the aramid fiber fabric and wet gel fiber fabric coated with the mixture layer by layer, let stand for 24 hours to obtain fiber prepreg, alternately stack the fiber prepregs, place them in a mold with a release cloth, wrap tin foil on the outer layer of the mold, place the mold in a double-layer flat-plate vulcanizing hydraulic press, perform curing treatment, cool to room temperature, and perform demolding to obtain a fiber textile composite material.

[0030] Comparative Example 3, a fiber textile composite material with high firmness, wherein the preparation method of the fiber textile composite material comprises the following steps: Step 1: nitrogen is filled into a reaction container, N-methylpyrrolidone and calcium chloride are added, the reaction container is placed in a water bath and stirred until the calcium chloride is completely dissolved, p-phenylenediamine is added to the reaction container after cooling to room temperature, the reaction container is placed in a freezing bath, phthaloyl chloride is added, and a magnetic stirrer is used to stir for 45 minutes, the reaction container is taken out and placed in a room temperature environment, and stirred to obtain a poly(p-phenylene terephthalamide) solution; Step 2: adding polyester chopped fibers to a poly(p-phenylene terephthalamide) solution, centrifuging with a high-speed centrifuge to remove bubbles in the solution, squeezing the degassed solution through a spinneret into a coagulation bath to obtain wet gel fibers, washing the wet gel fibers with deionized water and tert-butyl alcohol aqueous solution in turn, placing the treated wet gel fibers in a refrigerator for freezing treatment, placing the frozen wet gel fibers in a freeze dryer for drying treatment to obtain aerogel fibers, and weaving the aerogel fibers into aerogel fiber fabrics; Step 3: Mix the nano-lignin polyol-based epoxy resin, acetone solution, silane-modified alumina particles and curing agent, apply the mixture on wet gel fiber fabric and modified carbon fiber cloth, lay the modified carbon fiber cloth and wet gel fiber fabric coated with the mixture layer by layer, let it stand for 24 hours to obtain fiber prepreg, alternately stack the fiber prepregs, place them in a mold with a release cloth, wrap tin foil on the outer layer of the mold, place the mold in a double-layer flat plate vulcanizing hydraulic press, perform curing treatment, cool to room temperature, and perform demolding to obtain a fiber textile composite material.

[0031] Performance Testing Test 1 Tensile strength performance test: The fiber textile composite materials prepared in Example 1, Example 6, and Comparative Examples 1-3 were cut into samples with a size of 80 mm×10 mm, and the samples were clamped on the upper and lower clamps of a tensile testing machine, and the tensile load when the samples broke was recorded; Test 2 Impact toughness performance test: The fiber textile composite materials prepared in Example 1, Example 6, and Comparative Examples 1-3 were cut into samples with a size of 80 mm×10 mm, and placed in a sample impact testing machine to record the toughness strength of the samples; Table 1 Test results of tensile strength performance test

[0032] Table 2 Test results of impact toughness performance

[0033] Working principle: In the process of preparing wet gel fiber, adding polyester chopped fibers into poly(p-phenylene terephthalamide) solution can increase the stability of spinning solution and improve the mechanical strength of wet gel fiber. The lightweight characteristics of aerogel fiber increase the overall performance of fiber textile composite materials. Silane-modified alumina particles as fillers improve the corrosion resistance and thermal stability of fiber textile composites. Silane modification improves the dispersibility of alumina particles in epoxy resin and solves the problem of particle agglomeration affecting the performance of composite materials. The surface modification of carbon fiber and aramid fiber increases the roughness of the fiber surface, increases the mechanical bite force between the fiber and the epoxy resin, and improves the bonding force between the fiber and the epoxy resin, making the fiber textile composite material highly firm.

[0034] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high-strength fiber textile composite material, characterized in that: The invention comprises a fiber prepreg, and the preparation method of the fiber prepreg comprises the following steps: Step 1: Add polyester chopped fibers into a poly(p-phenylene terephthalamide) solution, use a high-speed centrifuge to centrifuge to remove bubbles in the solution, and squeeze the degassed solution through a spinneret into a coagulation bath to obtain wet gel fibers; Step 2: washing the wet gel fiber with deionized water and tert-butyl alcohol aqueous solution in turn, placing the treated wet gel fiber in a refrigerator for freezing treatment, placing the frozen wet gel fiber in a freeze dryer for drying treatment to obtain aerogel fiber, and weaving the aerogel fiber into aerogel fiber fabric; Step 3: Mix the nano-lignin polyol-based epoxy resin, acetone solution, silane-modified alumina particles and curing agent, apply the mixture on wet gel fiber fabric, modified carbon fiber cloth and aramid fiber fabric, lay the modified carbon fiber cloth, aramid fiber fabric and wet gel fiber fabric coated with the mixture layer by layer, let it stand for 24 hours, and obtain a fiber prepreg.

2. A high-strength fiber textile composite material according to claim 1, characterized in that: The preparation method of the poly(p-phenylene terephthalamide) solution comprises the following steps: Step 1: nitrogen is filled into a reaction vessel, N-methylpyrrolidone and calcium chloride are added, the reaction vessel is placed in a water bath and stirred until the calcium chloride is completely dissolved, and p-phenylenediamine is added to the reaction vessel after cooling to room temperature; Step 2: Place the reaction container in a freezing bath, add phthaloyl chloride, stir with a magnetic stirrer for 45 minutes, take out the reaction container and place it in a room temperature environment, stir to obtain a poly(p-phenylene terephthalamide) solution.

3. The high-strength fiber textile composite material according to claim 1, characterized in that: The preparation method of the modified carbon fiber cloth comprises the following steps: Step 1: Spread the carbon fiber cloth flat in the reaction tank, add acetone solution until the liquid level covers the carbon fiber cloth, and perform water bath treatment in a sealed space. Take it out after 2 days of water bath and wash it with distilled water; Step 2: Place the washed carbon fiber in a vacuum drying oven for drying, soak the dried carbon fiber cloth in concentrated nitric acid, wash with distilled water after a 3-hour water bath, and dry in a vacuum drying oven to obtain a modified carbon fiber cloth.

4. The high-strength fiber textile composite material according to claim 1, characterized in that: The method for preparing the silane-modified alumina particles comprises the following steps: Step 1: adding silane to an ethanol solution, stirring with a magnetic stirrer to obtain a silane ethanol solution, adding the ethanol solution to a reaction container, dissolving alumina particles in the ethanol solution, adding deionized water, placing the reaction container in a water bath, and continuously stirring to obtain a mixed solution; Step 2: slowly add the silane ethanol solution to the mixed solution, mix well and place in a water bath for stirring. After the reaction is completed, use a suction filtration device to filter the reaction solution, and wash with anhydrous ethanol after the filtration is completed; Step 3: Place the washed product in a drying oven for drying, and grind the product using a grinder to obtain silane-modified alumina particles.

5. The high-strength fiber textile composite material according to claim 1, characterized in that: The preparation method of the nano-lignin polyol-based epoxy resin comprises the following steps: Step 1: Add nano-lignin polyol and epichlorohydrin in a reaction container in sequence, stir with a magnetic stirrer, add bisphenol A particles, place the mixture in a water bath, and stir; Step 2: Add sodium hydroxide solution to the mixture, stir and mix, let it stand for 2 hours and then perform distillation treatment, cool the distilled product to room temperature to obtain nano-lignin polyol-based epoxy resin.

6. The high-strength fiber textile composite material according to claim 5, characterized in that: The preparation method of the nano-lignin polyol comprises the following steps: Step 1: dissolving the modified lignin in an ethylene glycol solution to obtain a lignin solution, placing the lignin solution in a water bath, stirring, and adding a sulfuric acid solution dropwise into the reaction solution to adjust the pH; Step 2: Filter the solution using hardened ash-free filter paper, pour the filtered solution into a dialysis bag, perform dialysis treatment in deionized water, add distilled water to dilute the treated solution, and perform ultrasonic treatment on the diluted solution to obtain a nano-lignin suspension; Step 3: Add ethylene glycol, propylene glycol and catalyst methanesulfonic acid to the nano-lignin suspension, place the mixture in an oil bath at 120° C. for 1 hour, cool to room temperature, add sodium hydroxide solution dropwise to the reactant, adjust the pH, and obtain nano-lignin-based polyol.

7. A high-strength fiber textile composite material according to claim 6, characterized in that: The preparation method of the modified lignin comprises the following steps: Step 1: adding lignin to distilled water, stirring with a stirrer to disperse the lignin in the water to obtain a uniform suspension, adding sodium hydroxide solution to the suspension, and stirring; Step 2: Add formaldehyde solution, place the mixed solution in a water bath for 5 hours, slowly add sulfuric acid solution after the reaction is completed, use a high-speed centrifuge for centrifugation, wash the product obtained by centrifugation with distilled water, and place the washed product in a vacuum drying oven to obtain modified lignin.

8. The high-strength fiber textile composite material according to claim 1, characterized in that: The preparation method of the aramid fiber fabric comprises the following steps: Step 1: dissolving calcium chloride in anhydrous ethanol to obtain an ethanol solution of calcium chloride, placing the aramid fiber in a reaction tank, immersing the aramid fiber in the ethanol solution of calcium chloride, and placing the reaction tank in a water bath; Step 2: Take out the aramid fiber, wash it with deionized water, put the washed aramid fiber in a vacuum drying oven for drying, and obtain aramid fiber fabric.

9. A method for preparing a fiber textile composite material with high firmness, applicable to a fiber textile composite material with high firmness as claimed in any one of claims 1 to 8, characterized in that: The preparation method of the fiber textile composite material comprises the following steps: S1. Stack the fiber prepregs alternately, place them in a mold equipped with a release cloth, and wrap the outer layer of the mold with tin foil; S2. Place the mold in a double-layer flat plate vulcanizing hydraulic press for curing, cool to room temperature, and demould to obtain a fiber textile composite material.

10. The method for preparing a high-strength fiber textile composite material according to claim 9, characterized in that: The method for preparing the composite material further comprises the following steps: S21. Clean the composite material after demoulding, remove excess demoulding cloth and resin, and cut the composite material according to needs.

Citation Information

Patent Citations

  • Novel method for preparing lignosulphonate epoxy resin

    CN101724136A

  • Raw materials and methods of manufacturing bio-based epoxy resins

    CN102558507A

  • Method for producing sodium lignosulphonate by utilizing residues obtained by producing ethanol with crop straws as raw materials

    CN102690423A

  • Preparation method of carbon cloth reinforced wet friction material

    CN103897334A

  • Aerogel thermal-insulation board and preparation method thereof

    CN108032564A